Three mild cases of coronavirus disease 2019 treated with saikatsugekito, a Japanese herbal medicine - Irie, Yasuhito (Traditional & Kampo Medicine, 2020)
CASES: We report cases of three patients infected with mild coronavirus disease 2019 (COVID‐19) treated only with Kampo medicine and discharged from the hospital without symptom exacerbation. CASE 1: A 41‐year‐old healthy female suffering from headache, sore throat, and fever. Case 2: A 16‐year‐old healthy female sufferking from nasal congestion and taste disorder. Case 3: A 12‐year‐old healthy male suffering from nasal congestion and taste disorder. OUTCOME: The three patients were prescribed saikatsugekito. Cases 1 and 3 initially presented with white and yellow tongue coating, which disappeared several days after the prescription of saikatsugekito. All three patients were discharged from the hospital without symptom exacerbation. CONCLUSION: We believe that treatment with Kampo medicine, which is relatively safe clinically and has few side effects, should be taken at an early stage of COVID‐19 along with coping therapy. And we think that saikatsugekito may contribute to prevent the worsening of COVID‐19.